Raf-1 and p21v-ras cooperate in the activation of mitogen-activated protein kinase. - Williams, N G (1993)
Mitogen-activated protein (MAP) kinases Raf-1, pp60src, and p21ras all play important roles in the transfer of signals from the cell surface to the nucleus. We have used the baculovirus/Sf9 insect cell system to elucidate the regulatory relationships between pp60v-src, p21v-ras, MAP kinase (p44erk1/mapk), and Raf-1. In Sf9 cells, p44erk1/mapk is activated by coexpression with either v-Raf or a constitutively activated form of Raf-1 (Raf22W). In contrast, p44erk1/mapk is activated to only a limited extent by coexpression with either Raf-1 or p21v-ras alone. This activation of p44erk1/mapk is greatly enhanced by coexpression with both p21v-ras and Raf-1. Since we have previously shown that p21v-ras stimulates Raf-1 activity, the activation of p44erk1/mapk by p21v-ras may occur exclusively via a Raf-1-dependent pathway. However, a dominant-inhibitory mutant of Raf-1 (Raf301) does not block the activation of p44erk1/mapk by p21-v-ras. Further, pp60v-src, which activates Raf-1 at least as effectively as p21v-ras, fails to enhance p44erk1/mapk activity greatly when coexpressed with Raf-1. These data suggest that activation of p44erk1/mapk by p21v-ras may occur via both Raf-1-dependent and Raf-1-independent pathways.